Perkembangan Kota Yogyakarta Berdasarkan Peningkatan Pemanfaatan Lahan - Novida Abbas; Enny Ratna Dewi (Balai Arkeologi Yogyakarta, 1995)
This paper tries to discuss the development of Yogyakarta City based on the land use model. Changes, both reduction and development, are clearly something that is experienced by the City of Yogyakarta, considering that until now the existence of the City of Yogyakarta has lasted almost a quarter of a century.